(untitled) (Ius Novum, 2022)
Liberalization of air transport services and changes in the external transportation policy of the EU caused that the economic regulation of the market is also changing. As a result, the standards that are in force based on bilateral agreements and laying down restrictive attitude towards access to the market of air transport are breached. The scope of regulations covered in international aviation agreements is also widened by the addition of issues that were subject to those agreements to a limited extent if at all. The article analyses those changes and evaluates them from the perspective of the regulation of access to aviation services among various states’ economies.